Association of Serum 25-Hydroxyl Vitamin D Deficiency and Age-Related Cataract: A Case-Control Study - Marwa Mahmoud Abdellah; Engy Mohamed Mostafa; Eman Hassan Salama; Eman Roshdy Mohamed (Journal of Ophthalmology)
Purpose. To study the relation between the serum 25-hydroxyl vitamin D (OH D) level and the occurrence of age-related cataract in a case-control study. Patients and Methods. 325 cataract patients and 385 control individuals of both sexes were examined for the 25-OH D level using the chemiluminescent microparticle immunoassay (CMIA) technology. Results. Mean 25-OH D level in cataract patients was 7.6 ± 5.5 ± 11.2 ng/mL and median was 5.6 (2.6–31.9), while in the control group, mean 25-OH D level was 18.5 ± 9.6 ng/mL and median was 17.8 (3.4–37.8) (p value < 0.001). There was a statistically significant difference among the different types of cataracts with the lowest level in nuclear cataract. Conclusion. 25-OH D levels in all enrolled individuals were below the reference levels with a severe deficiency in cataract patients. These results might highlight the role of deficiency of 25-OH D in age-related cataract patients.